1981
DOI: 10.1159/000182210
|View full text |Cite
|
Sign up to set email alerts
|

Renal and Cardiovascular Effects of Chronic Occlusion of the Bile Duct in Rats

Abstract: Rats subjected to chronic occlusion of the bile duct developed marked retention of sodium, expanded plasma volumes, increased renal vascular resistance, and a fall in renal blood flow and glomerular filtration rate. The cardiac output was low and almost all the animals were shown to have systemic endotoxemia. The purpose of this study was to investigate renal and cardiovascular function in unanesthetized rats with chronic obstructive jaundice. The results suggest the importance of a reduced cardiac output amon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1984
1984
2003
2003

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…In fact, the BDL model is characterized by poliuria [6,7], which is of uncertain origin. Possibly, the hyperbilirubinaemia or the elevated levels of bile acids are responsible for this alteration in water handling.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, the BDL model is characterized by poliuria [6,7], which is of uncertain origin. Possibly, the hyperbilirubinaemia or the elevated levels of bile acids are responsible for this alteration in water handling.…”
Section: Discussionmentioning
confidence: 99%
“…Several groups of authors have studied the cardiovascular and renal alterations that occur in this model [3][4][5][6][7][8], which reproduces some of the features of human cirrhosis. Thus chronic BDL induces a circulatory hyperdynamic state, with arterial hypotension and increased cardiac output, similar to that found in other experimental models of cirrhosis and in cirrhotic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Levels of NO and endothelial NO synthase (eNOS) protein expression are increased in aortic and pulmonary tissue, contributing to the vasodilation in those tissues (3,5,22). However, in the renal circulation, the site of vasoconstriction and reduced renal blood flow (RBF) during CBDL-induced cirrhosis (11,12,13,26), it is reasonable to hypothesize that eNOS protein expression and locally produced NO are decreased. In addition, recent studies have demonstrated that while NO is central to the vascular dysfunction during cirrhosis, there is a significant NO-independent component that contributes to the vascular dysfunction (2,3).…”
mentioning
confidence: 99%
“…volume, and splanchnic blood flow, and decreased peripheral resistance that leads to a decreased mean arterial pressure (MAP) [1]. Yet, despite the hyperdynamic circulation and prominent peripheral vasodilation, the renal vasculature is markedly vasoconstricted and renal sodium and water handling is impaired [2][3][4][5][6][7][8][9][10]. Because these alterations can precipitate many of the complications of liver disease, much effort has been aimed at elucidating the potential mechanisms that lead to the renal dysfunction.…”
mentioning
confidence: 99%